Generation of reticulocytes derived from human peripheral blood CD34ᶧ haematopoietic stem/progenitor cells for plasmodium knowlesi in vitro invasion assay - Mohamad, Fatin Sofia (2021)
Reticulocytes are specialised host cells for Plasmodium knowlesi, the fifth identified human malaria parasite. Yet, the availability of reticulocytes for P. knowlesi in vitro culture is restricted by the limited number of circulating reticulocytes in human peripheral blood (PB). Therefore, human PB-derived CD34+ haematopoietic stem/progenitor cells (HSPCs) with high proliferative potential were utilised in the present study as a source to generate sufficient supply of reticulocytes for P. knowlesi in vitro invasion assay. CD34+ HSPCs were expanded for 5 days in serum-free medium supplemented with expansion cytokines and growth factors. Expanded CD34+ HSPCs were then cultured with erythroid-supporting cytokines for 14 days for differentiation towards erythroid lineage to produce reticulocytes. The maturation of CD34+ HSPCs into reticulocytes was characterised by the expression of cell surface markers as well as the morphology of cells undergoing differentiation. The susceptibility of generated reticulocytes to invasion by P. knowlesi and P. falciparum (as a control parasite) was determined. After 5 days of expansion, the total cell population increased approximately 2.10 ± 0.10-fold in a culture initiated with CD34+ HSPCs. The commitment of CD34+ HSPCs towards the erythroid lineage was identified through a high expression of CD36/CD71 on day 11 and a decrease in expression of CD34 and CD45. Down regulation of CD36/CD71 expression on day 14 indicated that the maturation of normoblasts into reticulocytes. The morphological analysis revealed the presence of proerythroblasts, a large nucleated cell on day 8. The progression of proerythroblasts into normoblast was observed on day 11 by a decrease in cell size. Enucleated cells with at least three dots of cresyl blue ribonucleic acid (RNA) were recognised as reticulocytes and reached its maximum at 30.00 ± 1.76% on day 14. The invasion assay showed that P. knowlesi invaded CD34+ HSPC-derived reticulocytes, which was confirmed by Giemsa stained observations at 24-hour post-inoculation, however, with lower invasion index, 1.20 ± 0.33%. Meanwhile, P. falciparum efficiently invaded CD34+ HSPC-derived reticulocytes which was observed at 41-hour post-inoculation with an invasion index of 2.60 ± 0.11%. In conclusion, human PBderived CD34+ HSPCs could be considered as a potential source to generate reticulocytes required for P. knowlesi continuous in vitro culture.